Treasure hunters in trouble [an unofficial minecrafter's novel] - Morgan, Winter (New York Sky Pony Press, 2015)
Steve enlists the help of his friend Kyra to rescue Max, Lucy, and Henry, who have gotten lost in a treasure-laden temple.
4.6
Keywords: Buried treasure -- Fiction; Minecraft (Game) -- Fiction; Computer games -- Fiction; Adventure fiction